Research on Impact Performance of Hydraulic Rock Drill with Floating Characteristics of Double Damping System - Yelin Li; Zeng Bin; Yi Tu (Shock and Vibration)
As a technological innovation of high-power hydraulic rock drill, double damping system has a very important effect on impact performance. The double damping system is a floating mechanism. The characteristics of the floating mechanism have an important influence on the impact energy, frequency, and power of the hydraulic rock drill. Based on orifice throttling theory, the static equilibrium position of a damping piston was calculated, and the characteristic parameters of the double damping system were summarized as damping flow (Qd) and feed force (Fd). According to the characterization parameters of the double damping system, an experimental scheme of the floating characteristics of the double damping system was designed, and the combined experimental data of Qd and Fd were obtained. The 40 groups of experimental data were extracted, and the relationship between the combination (Qd, Fd) and impact energy and frequency and power were analyzed. The combination (Qd, Fd) with maximum and minimum power was selected to analyze the motion law of an impact piston. The maximum drilling power was obtained at the combination (Qd = 8 L·min−1, Fd = 16.25 kN). The influence factors of the double damping system on impact performance were summarized, and the characteristics of the double damping system under optimal impact performance were obtained.